The satisfaction of clients and caregivers with telehealth speech-language pathology services - Reem S. W. Alyahya (Digital Health)
Objectives To investigate the satisfaction of service users with different aspects related to telehealth speech-language pathology (SLP) services, and examine the influence of client's demographics, medical diagnosis, and type of clinical services on the level of satisfaction with telehealth services. Methods A questionnaire was developed and validated to measure the satisfaction of clients and caregivers with telehealth services. Phone survey was used to collect data from clients and caregivers of clients who received telehealth SLP services. Results 302 clients and caregivers completed the survey. Most of the respondents were strongly satisfied with different aspects related to telehealth, including their whole telehealth experience (82.12%), the perceived benefits from telehealth (69.21%), and the perceived quality of healthcare received through telehealth (87.75%). The levels of satisfaction with these aspects were not related to age or gender, but they were significantly influenced by the SLP diagnosis ( p  < 0.001). The results also showed high levels of satisfaction across all types of clinical services, including screening, assessment, therapy, and monitoring. There were no significant relationships between the types of clinical services and the levels of satisfaction with telehealth. Conclusions Most clients and caregivers were satisfied with SLP services received via telehealth irrespective of the type of clinical service, client's age, or gender. However, satisfaction with SLP telehealth and patient experience varied according to the client's diagnosis. These factors must be considered by policy makers and funding bodies while planning the implementation or expansion of telehealth SLP services.